L’aqueduc du Gier : étude des ponts-siphons du Garon à Brignais et Chaponost (Rhône) et de Beaunant à Sainte-Foy-lès-Lyon (Métropole de Lyon) - Kilian Blanc; Laurie Danielou (Gallia)
A combined study of the construction and materials was carried out on the Beaunant and Garon venter bridges within the framework of two doctoral theses undertaken at Lumière Lyon 2 University. This work forms part of the “construction” component of the Quatre aqueducs lyonnais Group headed by Aldo Borlenghi (Lyon 2 University) and Catherine Coquidé (Inrap).The Beaunant and Garon venter bridges are remarkable for their state of preservation and constitute a unique material for the study of this type of structure. They were both built in an unusual way: initially constructed with openings between the piers for either economic or aesthetic reasons, the bridges were subsequently filled in because of the risk of the piles collapsing. It is not known when this blocking was done, but it was probably not long after construction given the similarities between the original facing and the backfill. The aim of this dual study of construction and materials was therefore to understand how the piers were built, and why and how the arches were filled in. The construction study was based on photogrammetric surveys and a complete examination of all the architectural building blocks. Samples of stone, brick and mortar were taken from the original piles and the backfill of both bridges in order to identify the different materials employed. This dual study also compared the two bridges which –though different in their development– were built in the same way. The two venter bridges were made using the opus reticulatum mixtum technique, where square-headed pyramidal rubble stones are arranged at an angle of 45° in alternation with double layers of brick. When the arches of the two bridges were filled in, the corner chains were dismantled to allow the filling to be put in place. The construction technique is the same for both the original piers and the backfill. The same materials are used. In other words, the aim was to perfectly match the two phases of construction. However, this twin study showed that, despite this apparent homogeneity, there were some differences between the original piers and the backfill. For example, monochrome facing can be observed on piers 8, 9, 10, 21 and 22 of the Beaunant bridge, while the facing on the original piers is two-coloured.In particular, a comparison between the two bridges shows a difference in the use of mortar on the two bridges. The lime mortar was made from the sand of the rivers flowing under the two bridges; the Yzeron in the case of the Beaunant bridge, the Garon in bridge. However, the main difference between the two bridges is the facing. Garon’s venter bridge has a monochrome facing made of local granite. In contrast, the facing on Beaunant’s venter bridge consists of two colours, alternating between black rubble and white rubble. The first is granite or gneiss, a local rock. The second is imported limestone. The use of limestone is increasingly common in the Gier aqueduct near Lyon.In conclusion, the joint study of construction and materials led to new observations and new ideas about the construction technique employed on the Gier aqueduct and the materials used.